Lingkungan Usaha yang Mendukung Transformasi Usaha Mikro, Kecil dan Menengah di Era Revolusi Industri 4.0 - Tri Joko Wibowo (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
The Industrial Revolution 4.0 raises threats and opportunities for innovation for entrepreneurs. The competitive environment in this era is collaboration between business people and sharing economy. The success of an entrepreneur in managing the business of MSMEs is largely determined by many things. Support from various stakeholders is needed so that the SME business environment can be created in accordance with the competitive situation in the industrial era 4.0. The purpose of this paper is to conduct a review literature to find out how to encourage and transform MSMEs to be able to take advantage of the industrial era 4.0. The literature study was conducted to find out the critical factors faced by MSMEs to be able to compete in the era of industrial revolution 4.0. Various information is collected from journal searches with a search engine (google) and various up-to-date online news. Information is obtained that critical factors can be categorized into internal and external. Internal critical factors in the form of information technology adoption capabilities (big data & e-commerce) and changes in mindset & business competencies from aspects of business strategy, culture and business processes. External critical factors include government regulations both legal, IT and business infrastructure and market competition with fellow business people. Success in managing these critical factors will directly impact the performance of entrepreneurs in managing MSMEs and indirectly to the economy. These relationships are shown in the form of a business environment model.